Effect of extreme conditions on athlete performance - Paul, A.; Hanna, K. (ISEA Engineering of Sport 14 Conference, 2022)
There was concern over the decision to hold the 2021 Summer Olympic Games in Tokyo`s sweltering summer. Tokyo's average temperatures in late July and early August are the highest for any host city going back to 1984. Heatstroke is likely to be the biggest weather-related threat to participants, which is caused by prolonged exposure to high temperatures and humidity with little to no wind and can result in fainting, seizures, or general exhaustion.